Effective Practices of Elementary School Heads in Single National Curriculum Implementation - Shehbaz, Iqra; Saleem, Rimsha; Qutab, Syeda Hareem (Annals of Human and Social Sciences, 2025)
Education is the backbone of a nation’s development. The Single National Curriculum (SNC) was established in order to guarantee equity and consistency in Pakistan's educational system. Previously, multiple curricula were taught across different school systems that was the cause of creating educational disparities. This study examines the perceptions and practices of elementary school heads in SNC implementation, focusing on challenges, preparedness, and resource availability. The study employed a survey research design based on Fullan’s Model of Educational Change (1991). A multi-stage cluster sampling technique was used, selecting 250 school heads from Punjab. A validated questionnaire addressing important aspects like vision building, initiative, staff development, monitoring, and restructuring needs was used to gather data. The results show that school administrators have a favorable opinion of SNC and recognize its potential advantages.